PENGIMPLEMENTASIAN ANDROID DALAM PERANCANGAN APLIKASI NUSA MANDIRI MOBILE APPLICATION (NUMA) DENGAN PEMROGRAMAN JAVA - Windu Gata; Grace Gata; Nia Kusuma Wardhani (Universitas Budi Luhur, 2012)
Android is an operating system for mobile phones based on Linux. Android provides an open platform for developers to create their own applications for use by a variety of mobile devices. Android has various advantages as software that uses computer code base that can be distributed openly (open source) so that users can create new applications therein. Currently provided Android SDK (Software Development Kit) as a tool and APIs necessary to begin developing applications on the Android platform using the Java programming language. Application NUMA (Nusa Mandiri Mobile Application) was based on android to give to students in order to access the value directly using a mobile device.Keywords : Mobile Application, Pemrograman Java, Android, Perancangan Aplikasi